2016
DOI: 10.1111/eea.12465
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness attributes of a field population of the potato tuberworm, Phthorimaea operculella

Abstract: The potato tuberworm, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae), is a worldwide pest of solanaceous crops especially devastating to potatoes. In the present study, we investigated the cold hardiness profile of acclimated and non-acclimated immature and adult stages of a field population of P. operculella. For both acclimated and non-acclimated individuals mean supercooling point (SCP) did not differ significantly among developmental stages. Unlike supercooling capacity, acclimation at 5°C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
(78 reference statements)
0
10
1
Order By: Relevance
“…The lowest supercooling point of eggs and early larvae may be due to their small sizes (Carillo & Cannon 2005;Hahn et al 2008;Zheng et al 2011;Hemmati et al 2014). However, in contrast to Iranian and Korean populations of PTM, Andreadis et al (2016) found the lowest SCP for adults and last instar field-collected larvae for the Greek population of PTM. They also found the early stage larvae have a lower SCP than later stages, because of the higher amount of glycerol and other small cryoprotectants.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The lowest supercooling point of eggs and early larvae may be due to their small sizes (Carillo & Cannon 2005;Hahn et al 2008;Zheng et al 2011;Hemmati et al 2014). However, in contrast to Iranian and Korean populations of PTM, Andreadis et al (2016) found the lowest SCP for adults and last instar field-collected larvae for the Greek population of PTM. They also found the early stage larvae have a lower SCP than later stages, because of the higher amount of glycerol and other small cryoprotectants.…”
Section: Discussionmentioning
confidence: 76%
“…It is well documented that the low temperature stimulates the production and accumulation of the cryoprotectant elements in the insect body (Storey & Storey 1996;Fuller 2004;Storey & Storey 2012;Cha & Lee 2016). Survival at subzero temperature of PTM was studied by Langford (1934), Hemmati et al (2014) and Andreadis et al (2016). Khani et al (2007) found that the elevated amount of trehalose in overwintering larvae is correlated with a very low supecooling point in December rather than in larvae collected in autumn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported that these pests are causing severe damage to tomato and tobacco crops (Aryal & Jung, ; Vanevagancheva, Atanasova, & Dimitrov, ). PTMs have high reproductive potential and can, by parthenogenesis (Liu et al, ), become highly tolerant to a wide range of temperatures (Andreadis, Poulia, Noukari, Aslanidou, & Savopoulou‐Soultani, ; Sporleder, Kroschel, Quispe, & Lagnaoui, ) and resistant to pesticides (Doğramaci & Tingey, ; El‐kady, ), making them difficult to control. Accurate determination of the number of instars in pests is the basis for life table analyses, forecasting the outbreak of pest insects, key factor analyses and other aspects of integrated pest management programmes (Logan, Bentz, Vandygriff, & Turner, ).…”
Section: Introductionmentioning
confidence: 99%